Orbital metastasis of renal cell carcinoma masquerading as thyroid ophthalmopathy - Smrti Aravind, MBBS; Dhiran Sivasubramanian, MBBS; Sathwik Sanil, MBBS; Sharan Prasaanth, MBBS; Virushnee Senthilkumar, MBBS (Radiology Case Reports)
Renal cell carcinoma (RCC) is the most common kidney malignancy in adults. However, its presentation with orbital metastasis as the first clinical manifestation is extremely rare and can mimic several other conditions. We report the case of a 72-year-old woman with a history of hyperthyroidism, who presented with symptoms resembling thyroid ophthalmopathy. However, magnetic resonance imaging (MRI) of the orbit revealed orbital metastasis. To find the primary tumor, a surveillance computed tomography (CT) was done which showed a mass in the left kidney suggestive of RCC. Histopathological analysis of the mass confirmed clear cell RCC. Early identification of orbital metastases in RCC is crucial, as it may indicate advanced disease. Misdiagnosis due to similarities with other orbital conditions can lead to delayed treatment and suboptimal outcomes. This case highlights the pivotal role of radiological imaging in guiding the diagnosis and management of orbital metastases from RCC.